Changes in intestinal microbiota in patients with pancreatic cancer: a systematic review and meta-analysis - Liang, Meng; Liu, Zheng; Zhang, Rui; Yang, Ji-Hong; Wang, Xiao-Wei; Zhang, Nan (Frontiers in Microbiology, 2025)
BackgroundPancreatic cancer (PC) is a highly aggressive malignancy with an asymptomatic early stage, often resulting in rapid invasion of adjacent tissues and organs and a high mortality rate. Recent research has increasingly examined the gut microbiome as a potential factor in PC pathogenesis. Although changes in gut microbiota composition have been reported in patients with PC, a comprehensive evaluation of the relationship between gut microbiota and PC has not been systematically conducted.MethodsA systematic search of PubMed, Web of Science, Embase, and Cochrane databases was conducted, and a meta-analysis was performed on 10 studies including a total of 324 patients with PC.ResultsThe meta-analysis did not identify a statistically significant difference in α-diversity and microbial richness between patients with PC and those in the control group. However, a decrease in Bacteroides, Neisseria, Porphyromonas, Prevotella, and Actinomyces was observed in patients with PC, while Fusobacterium, Rothia, Streptococcus, Veillonella, and Escherichia-Shigella levels were increased.ConclusionThis meta-analysis demonstrates an association between PC and changes in gut microbiota composition at both the species and genus levels.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/recorddashboard, identifier CRD42023468159.